Politics of the Person as the Politics of Being - Walsh, David, 1950- (Book collections on Project MUSE., 2016)
Readers expecting a traditional philosophical work will be surprised and delighted by David Walsh's Politics of the Person as the Politics of Being, his highly original reflection on the transcendental nature of the person. A specialist in political theory, Walsh breaks new ground in this volume, arguing, as he says in the introduction, "that the person is transcendence, not only as an aspiration, but as his or her very reality. Nothing is higher. That is what Politics of the Person as the Politics of Being strives to acknowledge." The analysis of the person is the foundation for thinking about political community and human dignity and rights. Walsh establishes his notion of the person in the first four chapters. He begins with the question as to whether science can in any sense talk about persons. He then examines the person's core activities, free choice and knowledge, and reassesses the claims of the natural sciences. He considers the ground of the person and of interpersonal relationships, including our relationship with God. The final three chapters explore the unfolding of the person, imaginatively in art, in the personal "time" of history, and in the "space" of politics. Politics of the Person as the Politics of Being is a new way of philosophizing that is neither subjective nor objective but derived from the persons who can consider such perspectives. The book will interest students and scholars in contemporary political philosophy, philosophy of religion, and any groups interested in the person, personalism, and metaphysics. -- Provided by publisher.